(untitled) (Cuidado y Ocupación Humana, 2024)
The present study aimed to describe the relationship between dementia and performance in activities of daily living in older adults, considering its impact on autonomy and quality of life. A systematic review was conducted in databases such as PubMed, Scopus, and SciELO, using keywords in both English and Spanish related to older adults, dementia, independence, performance, and activities of daily living. Both institutional studies and full-text reflective articles were included, and a risk of bias assessment was performed through critical reading to ensure the methodological quality of the selected studies. A total of 50 studies that met the inclusion criteria were analyzed. The findings allowed the identification of six predominant types of dementia in the older adult population, including Alzheimer’s disease and vascular dementia. In addition, levels of dependency in the performance of activities of daily living were categorized, which facilitated the description of the relationship between different types of dementia and the degree of functional impairment in older adults. The results show that dementia directly influences the loss of independence and functional participation, highlighting the importance of personalized, timely, and occupation-centered interventions. These should not only aim to maintain autonomy but also to improve the overall quality of life and holistic well-being of older adults living with dementia.